Metode Pendidikan Dalam Perspektif Al-Quran dan Hadis - Nawazir, Safrudin; AM, Rusydi; Charles, Charles (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The aim of the research is to find out the educational method in the perspective of the Al-Quran and hadith. This study uses a qualitative approach, namely to describe and elaborate on educational methods from the perspective of the Koran and hadith. The data collection technique used in this research is library research (Library Research) where library research is the activity of collecting materials related to research originating from the Al-Qur'an, Hadith, books, scientific journals, literature and other publications that are worthy of being used as sources for research that will be examined by the author. The results showed that educational methods from the perspective of the Koran and hadith are: 1) the lecture method, 2) the method of discussion, question and answer or dialogue, 3) the method of raising awareness, 4) the method of giving rewards and punishments, and 5) the method of exemplary.